An overview of engineering properties and durability of glass fibre reinforced mixed plastic waste composite. (2022) - Gupta, Mayank; Yadav, Shalini; Kasar, Arnav Anuj; Khan, Md Umar
Abstract: In this research article a new class of epoxy- based glass fiber composite was prepared. Glass fiber was collected from the glass insulation factory. The Hand moulding method was used for the fabrication of composites. Composite fabricated with varying content ranges from 30 wt% to 50%. For a thorough characterization of GRP waste, detailed laboratory tests were performed. The results obtained from physic-chemical characteristics showed the bulk density of GRP waste as 0.84 g/cm 3, specific gravity 1.39 with pH and conductivity as 6.78 and 198.33 µS. Further, the results obtained from X-ray fluorescence (XRF) showed the presence of silica and calcium in appreciable amounts. Different mechanical properties like tensile test impact test, flexural test, were carried out hence low water absorption high flexure strength shows that it is suitable for construction purpose through eco friendly process. In physical properties water absorption test was done FTIR analysis is also carried out. Which shows that the silica content is higher in the glass fiber.